STUDI ANALISIS FAKTOR-FAKTOR PENGARUH KETERSEDIAAN INFRASTRUKTUR TRANSPORTASI SEPEDA DAN PEMILIHAN MODA TRANSPORTASI SEPEDA DI UNIVERSITAS INDONESIA - Gituri, Maulana Ichsan; Sumabrata, Jachrizal; Tjahjono, Tri (FSTPT Indonesia, 2015)
Universitas Indonesia as one of the campus that provides a wide variety of modes of transportation for campus visitors, one of them by providing bicycle transportation facilities A bicycle transportation research in UI campus is needed to determine the factors that influence the availability of bicycle transportation infrastructure for the academic community and the desire to use the bicycle transportation modes. This study uses survey and direct observation using the enclosed questionnaire addressed to the academic community of the University Indonesia. Analyzing the data with descriptive statistical and non-parametrical statistic methods , which determine the correlation and linear regression . The results of the analysis on bicycle transportation infrastructure assessment showed that the most influential variable powerful facilities. While the desire for cycling , reliability variable is the variable that most strongly influences.